PENYELENGGARAAN PERIZINAN BERUSAHA MENURUT PERATURAN DAERAH KOTA BOGOR NOMOR 1 TAHUN 2023 (STUDI KASUS RESTORAN MIE GACOAN) - Muhammad Arkaansyah; Ferry Edwar (Faculty of Law, Universitas Trisakti, 2023)
There are businesses in Bogor City that violate Article 10 of the Bogor Municipal Regulation No. 1, 2021 and do not have a business license. Its location is Mie Gacoan, located on Jalan Yasmin West Bogor. Originally, this Gacoan Mie restaurant had only NIB (Business Identification Number), i.e. corporate identity or registration mark. The government makes policy to govern the procedural arrangements established in accordance with the activities of Gacoan Noodles Restaurant. The question is whether the actions of the local government will be legally justified if the Mie Gacoan restaurant violates regulations in the Bogor city area but is allowed to continue as long as the regulations remain unclear. The research method used is normative research, the nature of the study is descriptive, the data used are primary and secondary data, library research is used to collect data, data analysis is qualitative, the inferential method uses deductive methods. Preferably, regional regulations should include general principles of good governance, licensing requirements and compliance with product standards such as the Job Creation Act and provisions of regional regulations. It should be consistent at Freies Ermessen.